The Western Sahara conflict: the dilemma of National Liberation War, Referendum and Terrorism in Africa`s last colony, 1973 – 2013 - Mordi, Emmanuel Nwafor (Penerbit UKM, 2015)
The Western Sahara conflict was studied, given its long duration and threat to the security of both North and West Africa. Years of national liberation war by the Polisario Front, and the failure of the United Nations, since 1991, to conduct a referendum to determine the issue of independence for the Sahrawis have bred frustration, and presented the resumption of suspended hostilities, and terrorism as a viable solution to Africa’s last war of independence. By interrogating diverse sources on this subject through the application of contemporary historical method, this study exposes the challenge of this prolonged conflict to the credibility of the AU and the UNO, and the danger posed by the availability of idle Polisario fighters for recruitment by terrorist groups, including Al Qaeda in the Islamic Maghreb. It concludes that only the UN implementation of its resolutions on the matter since 1963 could avert a descent into terrorism.